Lead Toxicity due to Ingestion of Lead-Contaminated Opium in a Patient Presenting with Motor Neuropathy and Upper Limb Paresis: A case report - Seyed M. M. Mirzaei; Ayob Akbari; Omid Mehrpour; Nasim Zamani (Sultan Qaboos University Medical Journal, 2019)
Opium users may present with central or peripheral nervous system-related symptoms, gastrointestinal complications and anaemia; in such cases, lead poisoning should be suspected and chelation therapy initiated as soon as possible. We report a 64-year-old male patient with a 20-year history of opium addiction who was referred to the Imam Reza Hospital, Birjand, Iran, in 2017 with severe motor neuropathy and paresis in both upper limbs. His primary symptoms were generalised weakness, abdominal and bone pain, constipation and lower limb paraesthesia that had started several months prior. In addition, he reported severe progressive bilateral paresis of the upper limbs of one month’s duration. A diagnosis of lead poisoning was confirmed by a blood lead level of 140 μg/dL. The patient underwent chelation therapy after which he improved significantly. At a one-year follow-up visit, he was neurologically intact and symptom-free.